Institutions and the Right to Vote in America - Kropf, Martha E.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
This book explores how the United States institutions of democracy have affected a citizen$1 (Bs ability to participate in politics. The 2000 election and the ensuing decade of research demonstrated that that the institutions of elections vitally affect participation. This book examines turnout and vote choice, as well as elections as an institution, administration of elections and the intermediaries that affect a citizen$1 (Bs ability to cast a vote as intended. Kropf traces the institutions of franchise from the Constitutional Convention through the 2012 election and the general themes of how institutions have changed increasing, democratization and production federal growth over time in the United States. .s
Chapter 1: Introduction -- Chapter 2: Institutions and the Norms That Help Maintain Stability -- Chapter 3: Chapter 3: The Multiple Laboratories of Democracy -- Chapter 4: The Federal Part of the Institution -- Chapter 5: Acquiring Voting Rights -- Chapter 6: Exercising the Right to Vote -- Chapter 7: Finding the Time and Place to Vote -- Chapter 9: Choosing Voters: Redistricting and Re-Apportionment -- Chapter 10: Implications of Institutionalism for Democracy -- Sources Cited.
Keywords: Political science; Democracy; Elections; United States -- Politics and government; Political Science and International Relations; Electoral Politics; US Politics; Democracy; Electronic books